Molecular characterization of soybean cyst nematode populations with different parasitism index to the Hartwig cultivar - Abdelnoor, Ricardo Vilela; Dias, Waldir Pereira; Silva, João Flávio Veloso; Marin, Silvana Regina Rockenbach; Kiihl, Romeu Afonso de Souza (Pesquisa Agropecuaria Brasileira, 2001)
Recently, a new race of soybean cyst nematode (SCN) (Heterodera glycines) was discovered, which breaks the resistance of cultivar Hartwig, resistant to all known races of SCN. This population was obtained from soybean plants collected in the Sorriso county, state of Mato Grosso, Brazil, and is characterized as race 4. To verify if this isolate was different from others classified as races 4 and 9, their genetic diversity was analyzed by using the RAPD technique. Nine populations of SCN were analyzed, and only four populations were able to parasitize soybean plants cultivar Hartwig. Based on this study, it was verified that the populations that break Hartwig resistance were different from the other populations. Based on cluster analysis, the populations were separated into three groups. Race 4 populations were placed in the first group, while the race 9 population was placed in the second group and those capable of breaking cultivar Hartwig's resistance were placed in group three. This work confirms that the SCN population found in Sorriso is different from other isolates classified as race 4, and was called race 4+.